Significant Luminescence Enhancement of Ga-Doped WS₂ Monolayers Grown by CVD - Zhang, S.; do Nascimento Barbosa, A.N.; Paiva de Araujo Monteiro de Barros, M.E.; Mello, A.; Lizárraga, K.; Venezuela, P.P.D.M.; Freire, F.L. (American Chemical Society, 2025)
Monolayer tungsten disulfide (WS₂) is a direct-band-gap semiconductor that has excellent luminescence properties, which are of great interest for optoelectronic applications. In this study, we investigated the effect of gallium (Ga) on WS₂ monolayers grown by chemical vapor deposition. Our results indicate that Ga-doped WS₂ exhibits a 3.6-fold increase in photoluminescence intensity for doped samples compared to pristine WS₂. To confirm the existence of Ga in the WS₂ structures, resonance Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were utilized as characterization methods. A redshift of the XPS spectrum was observed as well as an increase in the disorder-related Raman modes, which were attributed to the influence of Ga. XPS analysis and ab initio electronic structure calculations reveal the presence of substitutional Ga atoms as well as Ga atoms adsorbed on WS₂ surfaces.
Keywords: Luminescence; Monolayer; Doping; Materials science; Optoelectronics; Nanotechnology; https://purl.org/pe-repo/ocde/ford#2.10.01